2020
DOI: 10.23865/nse.v40.2601
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic Practice as Part of Work with Sustainability, Participation and Environment – Examples from a Finnish and Swedish Preschool

Abstract: The aim of the article is to highlight and discuss the relationship between core activities in early childhood and primary education, with a special focus on aesthetic practice in relation to sustainability, participation, project work and learning environments. The two preschools presented, one in Finland and one in Sweden, work with ecology and sustainable education in their daily practice. The result of the study comprises a presentation of and reflections on photographs as visual representations of educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Šorytė and Pakalniškienė"s (2019) research indicate that children"s opinions regarding the protection of environment is related to human beings and other elements of the nature and also children give statements about the importance of protecting human life, human health, animals and plants. In addition, research on early childhood education today indicates that children, parents and teachers do not focus only on local problems but they also focus on global problems such as making compost, reduction, reuse and recycling (Alıcı, 2013;Ärlemalm-Hagsér and Sundberg, 2016;Cengizoğlu, 2013;Güler-Yıldız et al, 2017;Häikiö et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Šorytė and Pakalniškienė"s (2019) research indicate that children"s opinions regarding the protection of environment is related to human beings and other elements of the nature and also children give statements about the importance of protecting human life, human health, animals and plants. In addition, research on early childhood education today indicates that children, parents and teachers do not focus only on local problems but they also focus on global problems such as making compost, reduction, reuse and recycling (Alıcı, 2013;Ärlemalm-Hagsér and Sundberg, 2016;Cengizoğlu, 2013;Güler-Yıldız et al, 2017;Häikiö et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to didactics, My Cookery aims to integrate experiential learning, student co-determination and the active use of taste competences during cooking (Leer & Wistoft, 2018). Recent research has shown that this combination of approaches shows good potential in enhancing student learning outcomes in food education (Christensen and Wistoft, 2016; Hansen et al, 2019 Häikiö et al, 2020; Mäkelä et al, 2018; Ozorak, 2013). However, the implementation of these didactics alongside the provision of children’s cookbook offers a unique way of applying these approaches, and therefore, research on the use of the method is also sparse.…”
Section: My Cookerymentioning
confidence: 99%
“…Research has shown over and over again that a nation that genuinely takes care of the education of its young has an assured successful future (Chong et al, 2021). Research from this perspective has also demonstrated that the earlier deliberate sustainable learning environments are created for the children, the better a competitive urge is created and given to them in terms of employment and further learning opportunities as well as the world of work, generally (Häikiö et al, 2020). Through this very early provision of sustainable learning environments, children grow to become genuinely productive citizens of a democracy.…”
Section: Introductionmentioning
confidence: 99%